O controle patrimonial como ferramenta de governança pública: o caso da Universidade Tecnológica Federal do Paraná - Fijor, Thiago Frederic Albert (2014)
The overall objective of this study is to analyze asset tracking of permanent property belonging to UTFPR, in all of its 13 campuses, as an Public Governance tool. The specific objectives were: to understand the principles of Public Administration and principles of Public Governance; describe the procedures, technologies and resources employed in asset tracking at UTFPR; attest that the principles of Public Governance through asset tracking at UTFPR have been observed; and lastly, propose solutions to improve the activity of asset tracking at UTFPR based on the principles of accountability and transparency of Public Governance. Because they are intended to meet a collective interest, public resources must be administered so as to maximize the benefits to the collectivity, abiding by the principles of legality, impersonality, morality, disclosure and efficiency. Internal and external control mechanisms have been implemented to prevent administrative acts from straying from this ideal. Asset tracking is a type of internal control that makes it possible to maintain updated information on permanent public assets, such as information on acquisition, asset record keeping and records on asset write-offs. To meet the objectives of the study, it was decided upon the qualitative research study method using the case study technique. A total of 21 servants were identified as responsible for asset tracking at the 13 UTFPR campuses. Another three servants were identified as contributing to the activity of asset tracking. The study used surveys, documental analysis, and analysis of technological devices. Content analysis was used as the method to examine collected materials. It was demonstrated that permanent asset tracking at UTFPR is currently not an efficient tool of Public Governance, considering the non-existence of transparency with regard to asset tracking. Likewise, the fulfillment of the principle of compliance has been compromised, as analytical data are not provided regarding the goods that comprise the assets of UTFPR. Moreover, the information provided in shortened format in management reports does not reflect reality, considering that inventories are not carried out in some campuses. In order to overcome these challenges, proposals include training, creation of norms regarding asset tracking, studies on the possibility of adopting new technologies, and effectively performing inventories in the campuses.